Uma poética amazônica: estudo do poema "A Uiara", de Octávio Sarmento - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This dissertation is based on studies on the literature produced in the Amazon by choosing Metaphor in the conception of Lakoff and Johnson (2002) as a method for the analysis of the poem "The Uiara" by Octavio Sarmento. The scope of the work is the reading of the metaphorical process throughout the text as a study of the journey of the Militão character, who moves from the northeastern backlands to the Amazon as an attempt to achieve a life without the same difficulties experienced during the drought. A narrative fabric with a strong appeal to the Amazonian imaginary that reveals several aspects of the region's culture, economy and social life in the late nineteenth and early twentieth centuries. Faced with this, the problematic question arises as to what are the implications of the Amazonian culture present in the mentioned text for the construction of the character Militão? How does the saga of this individual reveal the portrait of the dream and the frustration, the adventurous spirit and the escape of men who, once they arrive in the Amazon, would be integrated once and for all with a barbaric system by virtue of the exploitation of labor? Thus, in the light of the Theory of Conceptual Metaphor aims to understand the migratory journey of this character, as well as the cultural influences that he will suffer along the realization of the crossing between the crossed borders. In this sense, it was interesting to know how the metaphorical expressions revealed the stages of change of this drought trajectory, accompanied by a trait of the legendary (Uiara) as an understanding of a tragedy, among many others observed, in one of the peculiar phases of economic and social development of this part of the Brazilian territory, during the rubber period.
Keywords: Octávio Sarmento; Uiara; Poesia; LINGUÍSTICA, LETRAS E ARTES